Polygamy and Nikah Sirri Culture of Agen Thrifting Families in Teluk Nibung: An Islamic Family Law Perspective - Mardiana, Juli; Siddiq Turnip, Ibnu Radwan; Haekal, Fikri (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, Islamic family law regulates polygamy with clear provisions to ensure justice and the welfare of all parties involved. In reality, within the culture of Agen Thrifting families in Teluk Nibung, Tanjung Balai, polygamy and nikah sirri (unregistered marriages) are often adopted as strategies to circumvent stringent legal regulations, creating issues related to legal status and family rights. This study aims to examine the practices of polygamy and nikah sirri in the context of Agen Thrifting families, focusing on how these practices interact with Islamic family law provisions. This article is categorized as qualitative field research. The methodology employed is a juridical-empirical approach, combining legal analysis with direct field observations. The research findings indicate that the culture of polygamy among Agen Thrifting families is often accompanied by nikah sirri as an effort to evade strict legal regulations. This results in negative impacts, including family separation and unclear status of children. Such practices undermine the principles of Islamic family law, particularly the assurance of family rights protection and legal recognition in accordance with justice principles.